CULTURAL CONTENT ANALYSIS OF AN ENGLISH TEXTBOOK FOR FIFTH GRADE ELEMENTARY SCHOOL - Irma Wahyuni; Sulistiawati (Prodi Pendidikan Bahasa Inggris, STKIP Muhammadiyah Bogor, 2018)
Language and culture are related to each other. Being communicatively competent requires learners to understand the cultures. Teaching learners about cultural aspects may be effectively applied through textbook because it can be easily claimed that textbooks play vital role in English language teaching. The writer analyzed the cultural content of English textbook for 5th elementary school entitled Grow with English 2016 revised edition. This research aimed to describe types of cultures, how culture are represented in the textbook This research used descriptive qualitative method consists of content analysis to analyze the textbook. This research also adopted two frameworks from Cortazzi and Jin about types of culture and framework from Adaskou, Britten and Fahsi about sense of culture. The analysis found that English textbooks Grow With English for fifth grade dominantly presented through source culture compared to international culture and target culture. Secondly, the sense cultures were mostly represented by semantic sense compared to sociological sense, pragmatic sense, and aesthetic sense in textbooks. This research also found that there was an unbalanced quantity among presented types of cultures. In addition, every type and sense of culture contained in the English textbook is very important. The advantages of learning a language is that the students can learn culture at the same time, which can add insight to students.